Relationship Between Science and Religion in Wittgenstein’s Collection of Nonsense - Joseph Wang-Kathrein (Religions)
Ludwig Wittgenstein kept a box file titled “Nonsense Collection” that is now archived in the Research Institute Brenner-Archiv. Several items in this collection concern both science and religion (or spiritualism). Although Wittgenstein may have thought of them as jokes, these items do reflect his thoughts on the relationship between science and religion. In this paper, three items from the Nonsense Collection that touch both science and religion are presented. It will discuss first why these items are nonsensical by applying interpretation of the concept of nonsense given by McGuinness. Then it will take up different ideas of Wittgensteinian philosophy of religion proposed by Pichler, Schönbaumsfeld, Somavilla, and Sunday Grève; it shows that the items presented in this paper would also be nonsensical, according to this kind of philosophy of religion. It concludes with historical and modern cases that also show dysfunctional relationships between science and religion and that these cases may have found their way into the Nonsense Collection.